Prognostic value of 3-dimensional echocardiographical heart volume assessment in patients scheduled for left ventricular assist device implantation. (30th January 2018) - Otten, Albert; Kurz, Stephan; Anwar, Sibtain; Potapov, Evgenij; Krall, Christian; O'Brien, Benjamin; Habazettl, Helmut; Krabatsch, Thomas; Kukucka, Marian
Abstract: OBJECTIVES: Left ventricular assist device (LVAD) support is an increasingly important and successful therapeutic option for patients with end-stage heart failure. As chronic heart failure progresses, the left and right ventricles adapt by enlarging its volume and patients present for LVAD implantation with varying degrees of dilatation. By quantitatively assessing right ventricular (RV) and left ventricular (LV) volumes using 3D transoesophageal echocardiography and correlating the findings with clinical outcomes, we aim to investigate the prognostic value of LV and RV volumes for early survival after LVAD implantation. METHODS: This is a single-centre, non-randomized diagnostic cohort study using prospectively collected clinical and 3D echocardiographic data from 65 patients scheduled for LVAD implantation, using centrifugal pumps for long-term support (HeartWare and HeartMate 3). The primary end-point for this study is 60-day mortality, with longer term survival as a secondary end-point. RESULTS: We divided our cohort group into survivors and non-survivors at 60 days [49 patients (75%) and 16 patients (25%), respectively]. Right to left end-diastolic ratio assessed by 2D echocardiography was significantly higher in the 60-day non-survivors group (0.70 ± 0.09 vs 0.62 ± 0.11; P  = 0.01). Indexed end-diastolic volume parameters (LV, RV and overall heart) showed significant differences among the groups and were higher in the 60-day survivors group (LV volume 154 ± 51 ml/m 2 vs 110 ± 40 ml/m 2, P  = 0.004; RV volume 96 ± 27 ml/m 2 vs 80 ± 23 ml/m 2, P  = 0.05; heart 250 ± 64 ml/m 2 vs 190 ± 57 ml/m 2, P = 0.003). To investigate haemodynamic and echocardiographic parameters, the right to left end-diastolic ratio and indexed RV end-diastolic volume were associated with 60-day mortality in the logistic regression analysis. The Kaplan–Meier survival curves for patients with indexed RV end-diastolic volume >82 ml/m 2 vs indexed RV end-diastolic volume ≤82 ml/m 2 showed better 1-year survival ( P  = 0.005) for the group with more RV dilatation. CONCLUSIONS: Patients with moderately increased end-diastolic RV volume index carry a higher postoperative risk, while severe RV dilatation seems to be protective. In future, postoperative management of patients with moderately dilated RVs should be focussed on adjusting individually appropriate LVAD flows and providing frequent follow-up.